Steam Explosion Pretreatment Changes Ruminal Fermentation in vitro of Corn Stover by Shifting Archaeal and Bacterial Community Structure - Wang, Kun; Nan, Xuemei; Tong, Jinjin; Zhao, Guangyong; Jiang, Linshu; Xiong, Benhai (Frontiers in Microbiology, 2020)
Steam explosion has been considered to an environment-friendly pretreatment and broadly used for numerous lignocellulosic biomass. Steam explosion pretreatment improved fermentation efficiency and changed ruminal fermentation pattern of corn stover during ruminal fermentation in vitro. The study gave a comprehensive insight into how stream explosion pretreatment shifted archaeal and bacterial community structure to change ruminal fermentation in vitro of corn stover. Results showed that steam explosion pretreatment dramatically improved the apparent disappearance of dry matter, neutral detergent fiber and acid detergent fiber. Steam explosion pretreatment significant improved the concentration of total volatile fatty acids and decreased the ratio of acetate to propionate. At the archaeal genus level, steam explosion pretreatment significantly increased the relative abundance of Methanobrevibacter, which was recognized to be more efficient in methanogenesis. At the bacterial genus level, the shift in fermentation efficiency and pattern was achieved by increasing the relative abundance of cellulolytic bacteria and propionate-related bacteria, such as Prevotella, Treponema, Ruminococcus, Fibrobacter.